Some general settlements concerning criminology and the importance of the humanistic paradigm (Archives of Criminology, 2009)
The article presents a series of statements concerning criminology: it is a autonomous and multidisciplinary science; it should be separated from the criminal policy and merged with the study of social pathology. The distinction between descriptive and explaining criminology is of certain importance. In the latter, the problem of assumed paradigm is of particular importance. Approximately since l960, in social sciences and in criminology the antinaturalistic paradigm prevails. Its nature is raises controversies. The author thinks that the antinaturalistic paradigm – understood correctly – must be a humanistic paradigm based on the idea of "homo eligens" (a choosing man) and a moderate indeterminism. This point of view has many advantages: among others, it explains poor effects of the research in the etiology of crime and the difficulties in the struggle against crime. Criminology must be developed. That is relatively easy within descriptive criminology but significantly more difficult in explanatory criminology, where the more interesting information must be obtained from the criminal himself.